A COMMERCIALISED DURIAN PLANTATION: DEVELOPMENT AND DESIGN OF WEB AND MOBILE APPLICATION (Journal of Digital System Development, 2024)
Durian farmers face many challenges in managing their plantations efficiently and effectively. These challenges include unpredictable weather patterns, labour shortages, pest and disease outbreaks, market fluctuations, and the complexity of managing farm operations. The commercialisation of durian plantations represents a significant shift in the agricultural landscape, driven by increasing demand for this prized tropical fruit. This project focuses on developing and designing a comprehensive web and mobile application explicitly tailored for commercialised durian plantations in Malaysia. Employing the Rapid Application Development (RAD) approach, the project encompasses four main phases: analysis, rapid design, prototyping, testing, and deployment. By leveraging digital technology, the application aims to address these challenges by streamlining various aspects of durian plantation management, including crop monitoring, inventory management, pest and disease tracking, and yield forecasting. Through user-friendly interfaces and intuitive functionalities, the application seeks to empower durian growers with actionable insights and decision-making tools to navigate these challenges and enhance their operations' productivity, efficiency, and sustainability. An evaluation component was conducted to assess the usability and effectiveness of the application in real-world plantation settings. Overall, the response to the evaluation indicated that both applications are valuable and easy to use, justifying their integration into durian plantation management practices. The significance of this project lies in its potential to revolutionise durian plantation management practices, contributing to the broader goals of sustainable agriculture and economic development in the durian industry. Findings from the project evaluation will inform future directions for refinement and expansion of the application, ensuring its continued relevance and impact in supporting the growth and competitiveness of commercialised durian plantations.